Case report: Rehabilitation course in thrombocytopenia, anasarca, fever, reticulin fibrosis/renal failure, and organomegaly syndrome complicated by cerebral infarction in the left parabolic coronary region - Hashizaki, Takamasa; Nishimura, Yukihide; Kinoshita, Tokio; Minami, Kohei; Kawanishi, Makoto; Umemoto, Yasunori; Tajima, Fumihiro (Frontiers in Neurology, 2023)
Although thrombocytopenia, anasarca, fever, reticulin fibrosis/renal failure, and organomegaly (TAFRO) syndrome was first reported in 2010, its pathogenesis and prognosis are still unknown. Moreover, reports on rehabilitation in patients with TAFRO are limited. In severe cases, dyspnea and muscle weakness could impede improvements in activities of daily living (ADL). However, reports on exercise intensity showed no worsening of TAFRO within the load of 11–13 on the Borg scale. Herein, we describe the rehabilitation and progress in a 61-year-old woman with TAFRO syndrome complicated by cerebral infarction from early onset to discharge. After cerebral infarction onset in the perforating artery, she was admitted to the intensive care unit due to decreased blood pressure and underwent continuous hemodiafiltration. Two weeks following transfer to a general ward, the patient started gait training using a brace due to low blood pressure, respiration, and tachycardia. After initiating gait training, increasing the amount of training was difficult due to a high Borg scale of 15–19, elevated respiratory rate, and worsening tachycardia. Furthermore, there was little improvement in muscle strength on the healthy side after continuous training, owing to long-term steroid administration. On day 100 after transfer, the patient was discharged home with a T-cane gait at a monitored level. The patient had severe hemiplegia due to complications with severe TAFRO syndrome delaying early bed release and gait training; tachycardia; and respiratory distress. Additionally, delayed recovery from muscle weakness on the non-paralyzed side made it difficult for the patient to walk and perform ADLs. Despite these issues, low-frequency rehabilitation was useful. However, low-frequency rehabilitation with gait training, using a Borg scale 15–19 orthosis, did not adversely affect the course of TAFRO syndrome.